Protein engineering - Bocharov Eduard V.; Pavlov Konstantin V.; Volynsky Pavel E.; InTech
En este libro se cubren un amplio nm͠ero de tp̤icos mediante una base sl̤ida en ingeniera̕ de proten̕as, brindando conocimientos esenciales en el diseǫ y produccin̤ de estos compuestos. Se muestran diversos mťodos y aplicaciones en la materia a partir de contribuciones de distintos expertos alrededor del mundo. Lo anterior incluye el uso de aminoc̀idos no naturales, bioinformt̀ica, evolucin̤ molecular, plegamiento de proten̕as, entre otros. El documento est ̀comprendido por los siguientes capt̕ulos:Structure-Functional Insight Into Transmembrane Helix Dimerization Protein Engineering: Methods and Applications Evolutionary Engineering of Artificial Proteins with Limited Sets of Primitive Amino Acids Protein Engineering Applications on Industrially Important Enzymes: Candida methylica FDH as a Case Study Engineering High-Affinity T Cell Receptor/ Cytokine Fusions for Therapeutic Targeting Molecular Evolution Within Protease Family C2, or Calpains FN3 Domain Engineering Engineered Derivatives of Maltose-Binding Protein Applications of Bioinformatics and Experimental Methods to Intrinsic Disorder-Based Protein-Protein Interactions Protein Folding, Binding and Energy Landscape: A Synthesis Protein Engineering with Non-Natural Amino Acids Generation of Xylose-Fermenting Saccharomyces cerevisiae by Protein-Engineering In silico Engineering of Proteins That Recognize Small Molecules